In-vitro petal culture and callus formation in Rosa species - DATTA, S K; CHAKRABARTY, D; DEEPTI, DEEPTI; MANDAL, A K A; MISRA, P; SAXENA, M (The Indian Journal of Agricultural Sciences, 2014)
In an experiment conducted during 1999-2001 petals of 7 rose cultuvars [3 floribunda ('Contempo','America's Junior Miss' and 'Manasini'), 3 hybride tea ('Mrinalini','Preyasi' and 'Sylvia') and 1 grandiflora ('Queen Elizabeth')] were tested for regeneration in both Murashige and Skoog's and Schenk and Hildebrandt's medium with various concentrations and combinations of NAA, BAP, 2,4-D along with other medium composition. The callus formation was obtained in all the media tried, however no shoot organogenesis or somatic embryogenesis occurred. Thin layer chromatography (TLC) of different explants like callus, leaves and petals of different eges showed 17 spots of phenolic compounds having both qualitative and quantitiaive differences. similarly, spectrophotometic analyses showed different number of compounds in differnt explants. The gel electrophoretic patterns for soluble proteins indicated variation in nimber and intensity of bands within the callus (Total 8 bands) and other explants.Â